Extracellular vesicles as modulators of glioblastoma progression and tumor microenvironment - Jie Dai; Yong Jiang; Haoyue Hu; Shuang Zhang; Yue Chen (Pathology and Oncology Research, 2024)
Glioblastoma is the most aggressive brain tumor with extremely poor prognosis in adults. Routine treatments include surgery, chemotherapy, and radiotherapy; however, these may lead to rapid relapse and development of therapy-resistant tumor. Glioblastoma cells are known to communicate with macrophages, microglia, endothelial cells, astrocytes, and immune cells in the tumor microenvironment (TME) to promote tumor preservation. It was recently demonstrated that Glioblastoma-derived extracellular vesicles (EVs) participate in bidirectional intercellular communication in the TME. Apart from promoting glioblastoma cell proliferation, migration, and angiogenesis, EVs and their cargos (primarily proteins and miRNAs) can act as biomarkers for tumor diagnosis and prognosis. Furthermore, they can be used as therapeutic tools. In this review, the mechanisms of Glioblastoma-EVs biogenesis and intercellular communication with TME have been summarized. Moreover, there is discussion surrounding EVs as novel diagnostic structures and therapeutic tools for glioblastoma. Finally, unclear questions that require future investigation have been reviewed.